Pelatihan Penulisan Karya Tulis Ilmiah PPKn Dalam Menguatkan Kualitas Menulis Guru PPKn SMA Kota Surabaya - Suyono Suyono; Suhari Suhari; Bernadetta Budi Lestari; Khomsiyatil Askinah; Jihan Aulia Salma; Harlanda Almaratus Azahra (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The training for a scientific article for a surabaya city high school teacher is aimed at providing knowledge for a surabaya city general teacher who is not yet familiar with writing scientific articles, developing knowledge and adding to the quality of writing a scientific article for a counselor, and accompanying teacher for promotion. This training USES companion models, using talks, question-and-answer methods, and simulation methods. The target for this writing training isa high school counselor in the surabaya city of 30 participants. The value of this science - writing training is that teachers provide the incentive to make scientific articles and teachers have the expertise to do them and improve the teachers' professionalism